2020
DOI: 10.1371/journal.pbio.3000739
|View full text |Cite
|
Sign up to set email alerts
|

Increased prostaglandin-D2 in male STAT3-deficient hearts shifts cardiac progenitor cells from endothelial to white adipocyte differentiation

Abstract: Cardiac levels of the signal transducer and activator of transcription factor-3 (STAT3) decline with age, and male but not female mice with a cardiomyocyte-specific STAT3 deficiency conditional knockout (CKO) display premature age-related heart failure associated with reduced cardiac capillary density. In the present study, isolated male and female CKO-cardiomyocytes exhibit increased prostaglandin (PG)-generating cyclooxygenase-2 (COX-2) expression. The PG-degrading hydroxyprostaglandin-dehydrogenase-15 (HPGD… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Chronic inflammation underlies many forms of CVD ( 28 ). Administration of exogenous prostaglandins promotes a DCM-like phenotype of cardiomyocytes which further perpetuates prostaglandin secretion ( 32 , 33 ). Thus, a self-sustaining pro-inflammatory environment exists within the human DCM heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation underlies many forms of CVD ( 28 ). Administration of exogenous prostaglandins promotes a DCM-like phenotype of cardiomyocytes which further perpetuates prostaglandin secretion ( 32 , 33 ). Thus, a self-sustaining pro-inflammatory environment exists within the human DCM heart.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest differences in eicosanoid production and metabolism could explain sex-dependent differences in CVD risk and severity ( 47 ). Indeed, male DCM patients have been shown to have higher serum prostaglandin concentrations, which may suggest a greater involvement of pro-inflammatory eicosanoid signaling in male DCM patients ( 32 ). Apparent sex differences in EpFA:diol ratios may be attributed to higher expression of CYP2J2 in male DCM hearts, which did not reach significance in females.…”
Section: Discussionmentioning
confidence: 99%
“…PGJ2 is formed by dehydration within the cyclopentenone ring of PGD2 (Abdelrahman et al, 2004 ). Stelling et al ( 2020 ) reported that the PGD2 level was significantly increased in male mice cardiomyocytes with a cardiomyocyte-specific transcription factor-3 (STAT3) deficiency conditional knockout (CKO), which is an impairment of the endogenous cardiac regeneration potential as it shifts the differentiation potential of the cardiac progenitor cell (CPC) pool from endothelial cells toward white adipocytes, thereby promoting heart failure, a condition that impairs androgen receptor (AR) signaling in the absence of STAT3, which reduces the expression of the PG-degrading enzyme 15-hydroxyprostaglandin-dehydrogenase (HPGD). HDoHEs are biosynthesized from DHA, and the function is still not clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…(Yoon et al 2016 ), or BAY-u3405 (30 mg/kg, i.o.) (Stelling et al 2020 ) was administered at the same time as rGas6 1 day before BLM treatment. The inhibitor was administered once daily (AH-6809) or every two days (BGB324, NS-398, and BAY-u3405) following the first dosage, and mice were sacrificed 14 days after BLM treatment.…”
Section: Methodsmentioning
confidence: 99%